REVITALISASI LOKANANTA SURAKARTA - Nugrahani, Adysty; Samsudi, Samsudi; Purnomo, Agus Heru (Universitas Sebelas Maret Surakarta, 2017)
Abstract:Lokananta Surakarta be one proof of the historical progress of Indonesian music industry. However, because the decline since the late 80s caused by many things, Lokananta gradually dropped prestige resulting in the lonely recording and production activities that culminate in the building neglected and not maintained. In 2014, Lokananta including the 100 buildings and the heritage area of Surakarta, this became the basis for the existence Lokananta preserved and developed. The problem faced is how to revitalize Lokananta that can accommodate all the activities that take place in it by promoting the principle of preservation and revitalization of existing noticed that existed at this time. The purpose of the revitalization Lokananta is generating Lokananta that can accommodate recording activities, recreation, and education. The application of revitalization is done with the protection and maintenance of the main building as well as by adding facilities supporting the activities of musical performances both indoors and outdoors, as well as the infrastructure of leisure activities and education in the form of exhibition venues associated with the development of music and collections owned by Lokananta with regard to rules of preservation and revitalization, and with regard to existing conditions. Revitalization Lokananta Surakarta produce Lokananta able to accommodate the activities of recording, performances, recreation and education and support facilities which can provide added value to Lokananta.Â Keywords: Lokananta Surakarta, Revitalization, Conservation, Preservation